Effect of nitric acid on the pore structure and fractal characteristics of coal based on the low-temperature nitrogen adsorption method - Ni, Guanhua; Li, Shang; Rahman, Sheik; Xun, Meng; Wang, Hui; Xu, Yuhang; Xie, Hongchao (Powder technology, 2020)
To study the pore structure and fractal characteristics of acid-treated coal, in this paper, the low-temperature nitrogen adsorption method, scanning electron microscopy and the fractal theory were used to analyze the coal samples. The results show that the acid treatment enlarged the wedge-shaped hole into a cylindrical hole. Under the influence of HNO3, the ash, volatile and sulfur contents are negatively correlated with the fractal dimension of the pore surface (D1) and positively correlated with the fractal dimension of the pore structure (D2). And the specific surface area and total pore volume of the coal samples are positively correlated with D1 and negatively correlated with D2 after acid treatment. Influenced by the specific surface area and total pore volume, the relationship between the fractal dimension and adsorption is consistent with the relationship between the fractal dimension and specific surface area/total pore volume. [Display omitted] •The effect of acid treatment on coal quality was evaluated quantitatively.•The effect of acid treatment on adsorption property was investigated.•The relationship between fractal dimension and pore structure parameters is established.•The relationship between fractal dimension and coal characteristics is established.